Desde la red social Facebook: #NiUnaMenos en Lima 2016 - Cruz de la Torre, Jessica Daniela (Pontificia Universidad Católica del Perú, 2023)
In its inception, the social network Facebook was created for entertainment purposes. However, in this new digital age, interaction through social networks has become a new means to act. In these, a user can share a post or react to it if they feel it is aligned with their own interests. In this way, the user’s interest or emotions towards a certain cause or event are expressed and they can identify with it. One cause was to combat violence against women from the #NiUnaMenos social movement, in which they organized a massive march in August 2016 in Lima. In this article, it is attempted to find out how the use of Facebook influenced the formation of the aforementioned movement in Lima during 2016. It is proposed that it was done in two ways: as a means for collective mass organization for offline activities and as an instrument to build a discourse seeking to improve a situation through collective action. The methodology of this research is based on a balance of secondary sources that include: theses, magazine articles, books and other documents. Finally, it was found that Facebook provided specific tools for communication such as messaging, groups and a fan page. All of them helped the organization of the social movement #NiUnaMenos and were means by which immediate interaction and overcoming spatial limitations between people with similar interests was feasible, as well as the construction of a discourse around the situation of oppression and inequality that women experience through collective action.

En principio, la red social Facebook fue creada con fines de entretenimiento. Sin embargo, en esta nueva era digital, la interacción con relación a los medios sociales se volvió un modo de acción. En estas, se puede compartir o dejar determinada reacción a las publicaciones con respecto a los intereses de un usuario en específico. De esta manera, se manifiesta su interés por cierta causa y se identifica con ella. Una motivación fue combatir la violencia contra la mujer del movimiento social #NiUnaMenos que organizó una marcha masiva en agosto de 2016 en Lima. En el presente trabajo se busca averiguar de qué manera el uso de Facebook influyó en la conformación del mencionado movimiento en Lima durante el 2016. Se plantea que fue de dos maneras: como medio para la organización colectiva masiva para actividades offline y como instrumento para construir un discurso en búsqueda de mejorar una situación mediante la acción colectiva. La metodología de esta investigación se basa en un balance de fuentes secundarias que incluyen: tesis, artículos de revistas, libros y otros documentos. Finalmente, se encontró que Facebook proporcionó herramientas específicas como la mensajería, grupos y página de seguidores. Todas ellas ayudaron a la organización del movimiento social #NiUnaMenos y fueron medio por los cuales fue factible la interacción inmediata y la superación de limitaciones espaciales entre personas con intereses afines, así como la construcción de un discurso en torno a la situación de opresión y desigualdad que vivimos las mujeres mediante la acción colectiva.
Started on Facebook: #NiUnaMenos in Lima 2016
Keywords: #NiUnaMenos; Lima; Social movement; Digital platforms; Facebook; #NiUnaMenos; Lima; Movimiento social; Plataformas digitales; Facebook; https://purl.org/pe-repo/ocde/ford#5.04.01